Effect of Curcumin on Serum Cathepsin D in Patients with Metabolic Syndrome - Shirmohammadi, Leila; Ghayour-Mobarhan, Majid; Saberi-Karimian, Maryam; Iranshahi, Mehrdad; Tavallaie, Shima; Emamian, Marzieh; Sahebkar, Amirhossein (Cardiovascular & Haematological Disorders - Drug Targets, 2020)
Background: Inflammation has been shown to accompany Metabolic Syndrome (MetS) and its features. Cathepsin D is one of a proinflammatory mediator. In the current study, we aimed to investigate the effect of curcumin supplementation on serum cathepsin D levels in patients with MetS. Methods: The current study was conducted on 18-65 years old individuals with MetS diagnosed according to the International Diabetes Federation guidelines. A total of 80 participants were randomly divided into treatment and control groups. The first group (n=40) was given 2 capsules containing 500 mg of phosphatidylcholine complex of curcumin, and the other group (n=40) was given two 500 mg placebo capsules for 6 weeks. Before (week 0) and after (week 6) the intervention, anthropometric indices and blood pressure were measured and blood samples were taken. Serum cathepsin D was measured using an ELISA kit. Results: There was no significant difference between treatment and control groups in terms of weight, body mass index, waist circumference and serum cathepsin D levels before and after the intervention. In addition, there was no significant difference between pre- and post-trial values of serum cathepsin D. Conclusion: The present results do not suggest any effect of curcumin on cathepsin D levels in patients with MetS.
Keywords: osteoarthritis